Study and analysis of CMMRF for nano-finishing of aluminium alloy - Ghai, Viney (My University, 2015)
Aluminum alloys are widely used in optics as metallic mirrors, micro-electronics at fabrication level and micro-mechanical assemblies like high speed rotating systems towards improvement of friction factor & fatigue failure of rotating elements. In general, the ductile materials like Aluminum & Copper are being machined by Diamond turn machining (DTM) process to get nonmetric surface finish. However it is very difficult to achieve the required surface finishing (surface finish in order of nanometer or sub-nano meter) by conventional random finishing processes like lapping. With newly developed CMMRF (Chemo mechanical magneto rheological finishing) process, experimental trials have been carried out on Al-alloy by altering mechanical properties with the help of chemical reaction (varying type of chemical, type of abrasives and pH value) on the superficial layer of the material. On basis of these experimental trials, 85% improvement has been obtained. A full experimental design has been performed to optimize the process with varying few parameters like, concentration of chemicals, concentration of abrasives, concentration of carbonyl iron particles and working gap. Effect of different parameters has been studied. Average surface finish of less than 5 nm has been obtained, best surface finish of order 0.8 nm has been reported. Hence, the CMMRF process has capability to finish in sub nanometer level/ scale.
The experimental work has been carried out at Precision Engineering Division of BARC, Mumbai. ME-Production Engineering
Keywords: Aluminium; Mirror; Al-7075-T6; Surface finish; Polishing; CMMRF; production engineering; mechanical; med